2005
DOI: 10.1038/sj.gene.6364165
|View full text |Cite
|
Sign up to set email alerts
|

Association of MBL gene polymorphisms with major bacterial infection in patients treated with high-dose chemotherapy and autologous PBSCT

Abstract: A growing body of evidence indicates that genetic factors are involved in an increased risk of infection. We investigated whether mannose-binding lectin (MBL) gene polymorphisms that cause low levels of MBL are associated with the occurrence of major infections in patients, mainly bearing hematological malignancies, after high-dose chemotherapy (HDT) rescued by autologous peripheral blood stem cell transplantation (auto-PBSCT). A retrospective evaluation of 113 patients treated with HDT and auto-PBSCT revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 32 publications
4
42
0
Order By: Relevance
“…Horiuchi et al 24 found that the low producing genotypes B/B and B/A were associated with a highly increased and significant risk of major bacterial infections in a series of patients with mixed malignancies. In 113 patients, they found a much lower occurrence of bacterial infections (n ¼ 10) than we did (n ¼ 29, documented pneumonia Table 3 Multiple logistic regression analysis of risk of (a) breakthrough fever a (b) proven septicaemia a The relation between MBL2 polymorphisms and the function of the MBL system is complex, as significant variation between serum levels is seen within each genotype, 17,18 and the association found in the present study might be stronger, if serum levels of MBL are measured as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horiuchi et al 24 found that the low producing genotypes B/B and B/A were associated with a highly increased and significant risk of major bacterial infections in a series of patients with mixed malignancies. In 113 patients, they found a much lower occurrence of bacterial infections (n ¼ 10) than we did (n ¼ 29, documented pneumonia Table 3 Multiple logistic regression analysis of risk of (a) breakthrough fever a (b) proven septicaemia a The relation between MBL2 polymorphisms and the function of the MBL system is complex, as significant variation between serum levels is seen within each genotype, 17,18 and the association found in the present study might be stronger, if serum levels of MBL are measured as well.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that highfunctioning MBL genes decrease the risk of major bacterial infections. 24 Only one of the earlier published studies was made on a uniform group of patients, namely patients with AML, 21 and new studies on the topic should probably relate to specific patient groups. In this study, we focus on the impact of MBL2 polymorphism on the risk of severe infections related to ASCT in patients with MM.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the risk of fatal infectious complications is less than 5 % and may be even lower in experienced centres [17]. In the future, gene polymorphisms of components of the immune system may prove useful in refining the estimation of infection risks for individual patients [18]. While polymorphisms in Toll-like receptor [19] and cytokine genes are associated with the risk of invasive aspergillosis in allogeneic HSCT [20], mannose-binding lectin 2 gene polymorphisms are associated with severe infections in both allogeneic and autologous HSCT [21,22].…”
Section: Risk Stratification and Epidemiologymentioning
confidence: 97%
“…The incidence of febrile complications following HDC and auto-HSCT is 60-100 % [13,[16][17][18][19][20][21][22][23][24][25], whereas the majority is categorized as fever of unknown origin (FUO). One third of cases of documented infection [13,14] are mostly caused by bacteria.…”
Section: Risk Stratification and Epidemiologymentioning
confidence: 99%
“…In a series of 113 autologous HSCT for multiple myeloma, patients homozygous for wild-type mannose-binding lectin (MBL) 2 were at lower risk to develop septicemia compared with patients carrying the variant MBL2 [ 2 ]. In another study, MBL defi ciency was associated with higher risk of bacterial infections [ 3 ]. …”
Section: And 43 )mentioning
confidence: 99%